The Future of the Greek Economy Economic Development Through 2035 - Petrakis, Panagiotis E.; Kostis, Pantelis C.; Kafka, Kyriaki I.; Kanzola, Anna-Maria. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book introduces the Political Economy of Alternative Economic Futures for the Greek economy up to 2035. The analysis is not restricted to the presentation of a series of forecasts but aims to develop a comprehensive framework for Greece's future. The analysis covers five realms regarding alternative economic futures, which outline the political economy of Greece: sustainable development; sustainable governance; inclusive growth; evolution of human behaviors; and dynamic growth. A growth, an unsustainable growth, a transformation, and a falldown scenario are generated based on the severity of key-uncertainty factors' effects. Panagiotis E. Petrakis is the professor emeritus in the Department of Economics at National and Kapodistrian University of Athens (NKUA), Greece. He is the scientific coordinator of Distance Education Training Programs at the NKUA. He is the author of numerous monographs and has extensive publications in recognized academic journals on economic development, entrepreneurship, and cultural background. Pantelis C. Kostis is an assistant professor at the Department of Economics at the NKUA and a teaching staff at the Hellenic Open University, Greece. His research has been published in distinguished international academic journals including the Journal of Comparative Economics, Journal of Business Research, and Economic Modelling. He is also the co-author of several books regarding economic development and growth. Kyriaki I. Kafka is an adjunct lecturer of Economics at the Department of Economics at the NKUA, Greece. She has published books and articles in distinguished academic journals including the Journal of Comparative Economics, the Journal of Business Research, and the Journal of Innovation and Knowledge. Her research interests include economic development and growth, economic policy, economic shocks and uncertainty, entrepreneurship, and innovation. Anna-Maria Kanzola is a researcher in the Department of Economics at NKUA, Greece. She holds a B.Sc. degree with honors (9/10) in Economics from NKUA. Currently, she is working toward her M.Sc. at NKUA, in applied economics and finance. She works as a graduate research assistant at NKUA. She is mainly interested in microeconomics, macroeconomics, international economics, sociology, and anthropology.
Part A: Alternative Futures Analysis -- Chapter 1. Setting the Scenery: Factors Affecting the Future -- Chapter 2. Building Scenarios: the Four Economic Scenarios for Greek Alternative Economic Futures -- Chapter 3. Scenarios and Contextual Factors: Addressing the Implications.-Part B: The Past and the Present of the Greek economy. Chapter 4. Sustainable Development -- Chapter 5. Sustainable Governance -- Chapter 6. Inclusive Growth -- Chapter 7. Cultural Change and Development and Growth -- Chapter 8. The Dynamism of the Economy -- Part C: Alternative Futures for Greece: The Five Scenarios under the Five Pillars of Economic Development. Chapter 9. Alternative Economic Futures and Sustainable Development -- Chapter 10. Sustainable Governance and Alternative Economic Futures -- Chapter 11. The Impact of Alternative Economic Futures on Inclusive Growth -- Chapter 12. Cultural Change and Alternative Futures -- Chapter 13. The Dynamism of the Economy and the Alternative Futures.
Keywords: Economics; Economic development; Sustainability; Political Economy and Economic Systems; Economic Growth; Sustainability